(untitled) (Fiep Bulletin - online, 2019)
In recent years numerous activities have arisen in the context of physical exercise, as to physical development or bodyaesthetic, and one of these activities is Pilates. This study aims on identifying the early educational period of professionals whowork in Pilates studios in Joinville. The population / sample consisted of 64 professionals in the field of physiotherapy andphysical education working with Pilates in studios located in the city of Joinville / SC. The instrument was a questionnaire with questions related to professionals and studios’ owners where the practices take place in Joinville. The questionnaire wasproduced by the academic researcher with the researcher in charge and subjected to validation. The data were plotted on anExcel spreadsheet for Windows and later to the SPSS 16.0 for descriptive analysis from the tendency and associations. It waspossible to verify and conclude that the initial formation of professionals working in Pilates studios of Joinville region, are mostly inphysiotherapy. The lack of work on this line of research made it possible for this study to result relevant knowledge about aspectsof professional practice in Pilates studios which may lead to new researches on better understanding the current market.